2018
DOI: 10.1080/21645515.2018.1514353
|View full text |Cite
|
Sign up to set email alerts
|

Vaccine-related attitudes and decision-making among uninsured, Latin American immigrant mothers of adolescent daughters: a qualitative study

Abstract: Uninsured Latin American immigrant women are at increased risk for vaccine preventable diseases, such as cervical cancer; yet gaps in vaccine coverage persist. The purpose of this study was to explore vaccine-related knowledge, attitudes and decision-making for tetanus, diphtheria, and acellular pertussis (Tdap) vaccine, meningococcal conjugate vaccine (MenACWY), and human papillomavirus (HPV) vaccine among uninsured Latin American immigrant mothers of adolescent daughters. A purposive sample of 30 low-income,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 38 publications
1
35
0
Order By: Relevance
“…Our systematic review revealed certain attitude-related barriers to vaccine acceptability for adolescents, particularly vaccine hesitancy among some mothers. A qualitative study reported that Latin American immigrant mothers of adolescent daughters expressed more hesitancy regarding adolescent vaccines compared to childhood vaccines expressed an increased sense of belief in their ability to determine what is best for their children [48]. In contrast to the negative attitudes of immigrant parents as found in most of the included studies in our systematic review, most mainstream non-immigrant women had positive attitudes about receiving an HPV vaccine and high intention to receive the vaccine both for themselves and their daughters [49].…”
Section: Discussionmentioning
confidence: 99%
“…Our systematic review revealed certain attitude-related barriers to vaccine acceptability for adolescents, particularly vaccine hesitancy among some mothers. A qualitative study reported that Latin American immigrant mothers of adolescent daughters expressed more hesitancy regarding adolescent vaccines compared to childhood vaccines expressed an increased sense of belief in their ability to determine what is best for their children [48]. In contrast to the negative attitudes of immigrant parents as found in most of the included studies in our systematic review, most mainstream non-immigrant women had positive attitudes about receiving an HPV vaccine and high intention to receive the vaccine both for themselves and their daughters [49].…”
Section: Discussionmentioning
confidence: 99%
“…(E. Wang et al, 2015, p. 6706) In 23 studies, parents described how they perceived that the risk of adverse side effects from vaccines to be higher than the risk of acquiring vaccine-preventable disease Blaisdell et al, 2016;Dubé et al, 2016;Enkel et al, 2018;Gullion et al, 2008;Harmsen et al, 2013;Hatoková et al, 2018;Koski & Holst, 2017;McCoy et al, 2019;P. McDonald et al, 2019;Meleo-Erwin et al, 2017;Painter et al, 2019;Peretti-Watel et al, 2019;Reich, 2014Reich, , 2018Senier, 2008;Sobo et al, 2016;Swaney & Burns, 2019;Vandenberg & Kulig, 2015;E. Wang et al, 2015;Ward et al, 2017Ward et al, , 2018.…”
Section: Previous Experiencesmentioning
confidence: 99%
“…This belief was conflated with three ideas. First, parents claimed that vaccine-preventable diseases were easily treatable Blaisdell et al, 2016;Painter et al, 2019;Sobo et al, 2016;Vandenberg & Kulig, 2015). Under this idea, parents believed that they were capable of identifying the symptoms of vaccine-preventable disease and administering treatment themselves Blaisdell et al, 2016;Harmsen et al, 2013;Reich, 2014;Ward et al, 2017).…”
Section: Previous Experiencesmentioning
confidence: 99%
See 2 more Smart Citations